Myopericarditis and myositis in a patient with COVID-19: a case report. Issue 6 (30th October 2020) - Shabbir, Asad; Camm, Christian Fielder; Elkington, Andrew; Tilling, Lindsey; Stirrup, James; Chan, Antoni; Bull, Sacha
Abstract: Background: Concurrent myopericarditis and myositis can present in patients with pre-existing systemic inflammatory diseases. Here we present a case of myopericarditis and myositis associated with COVID-19, in the absence of respiratory symptoms. Case summary: We present a middle-aged female with a history of hypertension and previous myopericarditis. The patient was admitted with symptoms of central chest pain, and ECG and echocardiographic features of myopericarditis. Her symptoms did not improve, and CT thorax suggested possible SARS-CoV-2 infection for which she tested positive, despite no respiratory symptoms. Whilst on the ward, she developed bilateral leg weakness and a raised creatine kinase (CK), and magnetic resonance imaging (MRI) of her thighs confirmed myositis. A cardiac MRI confirmed myopericarditis. She was treated with colchicine 500 μg twice daily, ibuprofen 400 mg three times day, and prednisolone 30 mg per day, and her symptoms and weakness improved. Discussion: We describe the first reported case of concurrent myopericarditis, and myositis associated with COVID-19. Conventional therapy with colchicine, non-steroidal anti-inflammatory drugs, and glucocorticoids improved her symptoms, and reduced biochemical markers of myocardial and skeletal muscle inflammation.